N‐Glycosylation with Synthetic Undecaprenyl Pyrophosphate‐Linked Oligosaccharide to Oligopeptides by PglB Oligosaccharyltransferase from Campylobacter jejuni. Issue 5 (16th February 2015) - Ishiwata, Akihiro; Taguchi, Yuya; Lee, Yong Joo; Watanabe, Taisuke; Kohda, Daisuke; Ito, Yukishige
Abstract The oligosaccharyltransferase PglB from Campylobacter jejuni catalyses the N‐glycosylation reaction with undecaprenyl‐pyrophosphate‐linked Glc1GalNAc5Bac1 (Und‐PP‐Glc1GalNAc5Bac1). Experiments using chemically synthesized donors coupled to fluorescently tagged peptides confirmed that biosynthetic intermediate Und‐PP‐Bac1 and Und‐PP‐GalNAc2Bac1 are transferred efficiently to the Asn residue in the consensus sequence (D/E‐X′‐N‐X‐T/S, X′, X≠P). The products were analyzed in detail by tandem MS to confirm their chemical structures.